Penerapan Savitzky Golay Filter Pada Citra Hiperspektral Dari Buah Kelapa Sawit - Anand, Barri; Candra, Feri; Shiddiq, Minarni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
This research is entitled Application of SG Filter to Hyperspectral Image of Palm Fruit Head. This research is motivated by one of the biggest sources of livelihood for the Indonesian people, namely oil palm plantations. In measuring the maturity level of oil palm fruit in the next process, there is an obstacle in the form of hyperspectral data having a lot of noise. As a result of the large amount of noise, the hyperspectral image is not good. The impact is that the hyperspectral image cannot be processed and a program is implemented to overcome the maturity level of the palm fruit. The purpose of this study is to provide a solution to the problem of the amount of noise in a hyperspectral image, thus making the hyperspectral image smoother. The solution is to use SG Filter with the help of MATLAB software. The stages of this research began with literature study, data collection, method application, comparison of results, and conclusions. This study uses the SG filter to smooth the data with the help of the MATLAB program. The result of this research is a hyperspectral image model which is smoother without much noise. Keywords: Savitzky Golay Filter, MATLAB, Hyperspectral Imaging, Normalisasi